Magnitude and associated factors of needle stick and sharps injuries among health care workers in Dessie City Hospitals, north east Ethiopia - Solomon Assen; Mamo Wubshet; Manay Kifle; Tewelde Wubayehu; Berihu Gidey Aregawi (BMC, 2020)
Abstract Background Work-related exposures to needle stick and sharps accidents are essential reason of infections with blood borne pathogens amongst health care employees and can cause extensive fitness consequences and psychological stress. The aim of this study was to determine the magnitude of needle stick and sharps injuries and associated factors among health care workers in Dessie town hospitals. Method This institution-based cross-sectional study was conducted from March 21-April 21/2015, amongst health care people in Dessie city hospitals. Data have been collected by a structured and pre-tested questionnaire. The study included 438 health care employees who had been selected through the use of a simple random sampling technique. The gathered data have been checked, coded and entered to EPI-info version 3.5.1 and exported to SPSS model 20 for analysis. Bivariate and multivariate logistic regression analyses have been executed to identify elements related with the structured variable. Results From 457 selected study participants, 438 (95.8%) responded to the questionnaire. The magnitude of needle stick and sharps injuries in the last 12 months was 124(28.3%), of which 92(74.2%) was reported by males and the rest 32(25.8%) by females. Being male [AOR: 4.25, 95%CI:(2.43,7.41)],had no safety instructions in the work area [AOR:2.27,95%CI: (1.29,3.97)],had no training on safety and health [AOR:4.92,95%CI:(2.75,8.79)],had ≤5 years work experience [AOR:9.0,95%CI:(4.88,16.60)],recapping of used needle [AOR: 2.63, 95%CI: (1.39, 4.99)] were the variables that significantly associated with needle stick and sharps injuries. Conclusion This study showed still a high magnitude of needle stick or sharps among healthcare workers. Therefore, training on work related safety and wellbeing, making safety instructions accessible and avoiding a recap of the needle after use are important to reduce the chance of such injuries among healthcare workers.